Memory Expurgation? Cairo: A Comment on Photographs - Mona Abaza (Media Theory)
This short piece is a commentary on photographs taken in Cairo between 2011 and 2013. The country is currently experiencing a pervasive moment of erasure on the collective level, going hand in hand with a hard counter-revolutionary momentum. In this context, gazing at photographs might be an exercise in an ‘inner exilic’ form of remembrance. This article attempts to evoke snapshots of the performative street, while trying to reflect on the nostalgic sentiment that is omnipresent among various opposing camps to a degree that has not been seen before.